2020
DOI: 10.3390/app10113836
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Analysis of Fluorobenzenes via Multinuclear Detection in the Strong Heteronuclear J-Coupling Regime

Abstract: Chemical analysis via nuclear magnetic resonance (NMR) spectroscopy using permanent magnets, rather than superconducting magnets, is a rapidly developing field. Performing the NMR measurement in the strong heteronuclear J-coupling regime has shown considerable promise for the chemical analysis of small molecules. Typically, the condition for the strong heteronuclear J-coupling regime is satisfied at µT magnetic field strengths and enables high resolution J-coupled spectra (JCS) to be acquired. However, the JCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 67 publications
1
13
1
Order By: Relevance
“…Finally, the authors would like to correct the previously reported simulated errors on a system of fluorobenzene compounds simulations. 23 The quantitative results in the previous study produced larger errors than observed in the present study, even for simulated systems after accounting for the Ξ differences between 19 F and 1 H. In this case, normalizing the peaks by Ξ local was insufficient to rectify the errors in the simulation. The errors in quantitating the simulated spectra are on the order of 4−7% below the predicted stoichiometry and always tend to larger 19 F concentrations.…”
Section: ■ Experimental Sectioncontrasting
confidence: 61%
See 3 more Smart Citations
“…Finally, the authors would like to correct the previously reported simulated errors on a system of fluorobenzene compounds simulations. 23 The quantitative results in the previous study produced larger errors than observed in the present study, even for simulated systems after accounting for the Ξ differences between 19 F and 1 H. In this case, normalizing the peaks by Ξ local was insufficient to rectify the errors in the simulation. The errors in quantitating the simulated spectra are on the order of 4−7% below the predicted stoichiometry and always tend to larger 19 F concentrations.…”
Section: ■ Experimental Sectioncontrasting
confidence: 61%
“…A previous report had demonstrated quantitation of 19 F and 1 H, two spin-1/2 nuclei separated by only ∼140 Hz. 23 We have extended this to single spectrum detection of 7 Li and 1 H, in which the Larmor frequencies are separated by ∼1.2 kHz and contain a quadrupolar nucleus. The 7 Li and 1 H spin systems are uncoupled, and the JCS of the mixture is shown in Figure 2.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In [8], advances in the development of a Field Programmable Gate Array (FPGA) based spectrometers for NMR relaxation is described along with applications in NMR cryoporometry. Performing the NMR measurement in the strong heteronuclear J-coupling regime is described in [9] and shows promise for the chemical analysis of small molecules. The results demonstrate that high resolution J-coupled spectra are quantitative, and the common NMR observables, including Larmor frequency, heteronuclear and homonuclear J-couplings, relative signs of the J-coupling, chemical shift and relaxation times, are all measurable and are differentiable between molecules at low magnetic fields.…”
Section: Applications Of Low Field Magnetic Resonancementioning
confidence: 99%